Immediate complications and subsequent reproductive outcome after medical abortion: hospital based cross sectional study - Sathe, Parul Anuj; Chaudhari, Kamlesh R.; Parikh, Nirzar Samir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Medical abortion is considered to be a safe, effective and reliable method for termination of pregnancy. The procedure has stood the test of time very well over the last 10 years in terms of results and immediate complications but there are not many reports regarding the subsequent reproductive outcome of these women. Thus, it was decided to conduct a study with special focus on subsequent reproductive outcome in women undergoing medical abortion. The objectives of the study were to determine the source of health care provider for women seeking medical abortion, to study immediate complications of medical abortion, to study acceptance of family planning methods post medical abortion in the study subjects and to study subsequent reproductive outcomes in women who underwent medical abortion. Methods: A cross sectional institution based study was conducted after ethics committee approval in the Obstetrics and Gynecology outpatient department of a tertiary care institute from January 2014 to December 2014. 94 newly registered patients in the age group of 18-35 years who came to the Obstetrics and Gynecology OPD during the study period were interviewed. Amongst these those who have undergone medical abortion in the period between 2010 and 2011 and were willing to participate in the study were enrolled. Diagnosed cases of Diabetes Mellitus, Hypertension and any other major medical or surgical illness were excluded from the study. Study subjects were interviewed with a revalidated, pretested semi structured Questionnaire with due privacy to maintain confidentiality. The data was analyzed by SPSS version 16 software. Results: 13.8% study subjects took their medicines from chemists without consulting any medical professional and 9.5% of them were prescribed these medicines by general practitioners. Prevalence of immediate complications that is incomplete abortion, need for surgical evacuation and excessive bleeding in the study were 17%, 11.7% and 1.1% respectively. Proportion of women who accepted family planning post medical abortion was 62.8%. Prevalence of subsequent reproductive outcomes in females who did not use permanent method of sterilization or got copper T inserted were infertility (7.1%), abortion (8.9%), ectopic pregnancy (3.6%), PIH (10.7%), IUGR (3.6%) and preterm labour (10.7%). Conclusions: Medical abortion using Mifepristone and Misoprostol is a reliable and safe method of termination of early pregnancy (up to 7 weeks period of gestation). These findings are relevant while counseling patients for medical abortion.